Determination of Critical Powder Loading of Titanium-Hydroxyapatite with Powder Space Holder for Powder Injection Molding Feedstocks / Mohd Yusuf Zakaria...[et al.] - Zakaria, Mohd Yusuf; Sulong, Abu Bakar; Ramli, Mohd Ikram; Raza, Muhammad Rafi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Binder and powder formulation are crucial for powder injection molding (PIM) process that can be obtained based on critical powder volume percetange (CPVP) method. The binder is the main component for flowability of feedstock and proper composition can influence the feedstock whether can be injected, debinded and sintered without any defect. This study is focused on the determination of critical powder loading for titanium-hydroxyapatite (Ti-HA) with powder space holder for powder injection molding feedstock. The critical powder obtained at 82% of the powder with 90:10 ratios of the titanium and hydroxyapatite with 20% of a space holder. The optimal powder loading selected at 78%, which is 2~5% below to the critical powder loading value. Green part was successfully obtained without any physical defect using the optimal powder loading.